Research-based methods of reading instruction for English language learners, grades K-4 - Linan-Thompson, Sylvia, 1959- (Association for Supervision and Curriculum Development, 2007)
This book is packed with reliable, high-impact, flexible strategies for teaching and learning that are grounded in research and suitable for teachers at any level. The authors also explain how teachers can use an innovative visual profile to better plan for different teaching and learning styles in their classrooms.